Biological and Mechanical Evaluation of Novel Prototype Dental Composites. (January 2019) - Van der Laan, H.L.; Zajdowicz, S.L.; Kuroda, K.; Bielajew, B.J.; Davidson, T.A.; Gardinier, J.; Kohn, D.H.; Chahal, S.; Chang, S.; Liu, J.; Gerszberg, J.; Scott, T.F.; et al.
The breakdown of the polymeric component of contemporary composite dental restorative materials compromises their longevity, while leachable compounds from these materials have cellular consequences. Thus, a new generation of composite materials needed to be designed to have a longer service life and ensure that any leachable compounds are not harmful to appropriate cell lines. To accomplish this, we have developed concurrent thiol-ene-based polymerization and allyl sulfide–based addition-fragmentation chain transfer chemistries to afford cross-linked polymeric resins that demonstrate low shrinkage and low shrinkage stress. In the past, the filler used in dental composites mainly consisted of glass, which is biologically inert. In several of our prototype composites, we introduced fluorapatite (FA) crystals, which resemble enamel crystals and are bioactive. These novel prototype composites were benchmarked against similarly filled methacrylate-based bisphenol A diglycidyl ether dimethacrylate / triethylene glycol dimethacrylate (bisGMA/TEGDMA) composite for their cytotoxicity, mechanical properties, biofilm formation, and fluoride release. The leachables at pH 7 from all the composites were nontoxic to dental pulp stem cells. There was a trend toward an increase in total toughness of the glass-only-filled prototype composites as compared with the similarly filled bisGMA/TEGDMA composite. Other mechanical properties of the glass-only-filled prototype composites were comparable to the similarly filled bisGMA/TEGDMA composite. Incorporation of the FA reduced the mechanical properties of the prototype and bisGMA/TEGDMA composite. Biofilm mass and colony-forming units per milliliter were reduced on the glass-only-filled prototype composites as compared with the glass-only-filled bisGMA/TEGDMA composite and were significantly reduced by the addition of FA to all composites. Fluoride release at pH 7 was greatest after 24 h for the bisGMA/TEGDMA glass + FA composite as compared with the similarly filled prototypes, but overall the F - release was marginal and not at a concentration to affect bacterial metabolism.